Experience of women victims of violence about Maria da Penha Law - Evelyn Priscila Santinon; Dulce Maria Rosa Gualda; Edemilson Antunes Campos; Lucia Cristina Florentino Pereira Silva (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
The objective of this research is to understand the experiences of women victims of domestic and family violence, understanding the use of the Maria da Penha Law as a form of empowerment. Also, develop a social context and help to spread the knowledge of viable methods to combat it, especially the Maria da Penha Law. It is known that violence against women is the result of individual characteristics, contextual and environmental factors that, if present, increase the possibility. Are cited the ages, marital status or personality of individuals, living habits and the abuse of alcohol and illicit drugs, the social integration of the family involving low income, poor education and unemployment, or the role of gender in family relationships -- either present or historical in families. The goal is to help enrich the repertoire of the violence against women, offering subsidies for the establishment of public policies in several areas to minimize the problems of violence.